2007
DOI: 10.1108/02640470710729128
|View full text |Cite
|
Sign up to set email alerts
|

Electronic journals collections in Argentine private academic libraries

Abstract: Purpose -The aim of this research is to describe the impact that the emergence of electronic journals has exerted on different services and areas making up information units in Argentine private universities. Design/methodology/approach -The analysis focuses on the 27 libraries with journals that answered a survey, and impact is evaluated by means of the survey's closed and open questions. This research covers the following aspects: selection and acquisition, human resources, technical processes, informatics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The journal use study in the UK (Bonthron et al , 2003) indicated high use among faculty members as well graduate students and the highest users are the engineers, clinical medicine practitioners (>70 per cent), followed by the chemists (>60 per cent), pure and applied sciences and social sciences and the mathematicians. A recent study of electronic journals collections in Argentinian private academic libraries by Gonzalez Bonorini and Molteni (2007) indicated an increase in the use of electronic journals (40.7 per cent, 11 out of 27 libraries). This increase was attributed to user trainings, guidelines, manuals and tutorials prepared and delivered to users.…”
Section: Introductionmentioning
confidence: 99%
“…The journal use study in the UK (Bonthron et al , 2003) indicated high use among faculty members as well graduate students and the highest users are the engineers, clinical medicine practitioners (>70 per cent), followed by the chemists (>60 per cent), pure and applied sciences and social sciences and the mathematicians. A recent study of electronic journals collections in Argentinian private academic libraries by Gonzalez Bonorini and Molteni (2007) indicated an increase in the use of electronic journals (40.7 per cent, 11 out of 27 libraries). This increase was attributed to user trainings, guidelines, manuals and tutorials prepared and delivered to users.…”
Section: Introductionmentioning
confidence: 99%